Borneo Recipe - Waktu Saptu, Mohd Nur Fikri; Masidi, Amnizar Hirlizi; Johil, J Debbie Angellisa; Ahad, Nor Shahirah; Roslan, Rosdiana (2015)
The name of our company is Borneo Recipe. Borneo Recipe is a restaurant which promoting the culture foods of 5 major ethnic in Sabah, the menu of Borneo Recipe are consist of main menu that were famous among the ethnic but rarely to get nowadays if not directly from the certain ethnic to providing it during certain time or any event. People migrated to urban area can now experience their cultural food from their hometown and also promoting these cultural foods to tourists as an attraction. Other ethnic can also experience different ethnic's cultural foods. Other than that, young people can also knowing the foods so that these cultural foods can be preserve for our next generation.